Investigating skin cancer case reporting to The Health and Occupation Reporting (THOR) network. (19th October 2011) - Turner, Susan; Forman, Steven; McNamee, Roseanne; Carder, Melanie; Agius, Raymond
Abstract : Objectives: In 2008, the World Health Organisation reported that one in three cancers diagnosed is dermatological. Exposures that are associated with work-related skin malignancy include radiation (ultraviolet and ionising), polycyclic aromatic hydrocarbons, and arsenic; the commonest exposure being ultraviolet radiation. UK-wide surveillance schemes which capture case reports of work-related ill-health (such as THOR) allow investigation of changes over time of dermatological malignancies, in terms of incidence and exposure. The aim was to analyse changes over time in incidence of work-related skin malignancy, and to investigate time differences between exposure, symptom onset and case reporting to THOR. Methods: THOR data (1996–2009) reported under the skin surveillance scheme were analysed by diagnosis, occupation/sector of employment, and chronicity of exposure in relation to symptom onset and case reporting. Results: The majority of the 1988 cases (1972 = 99%) were associated with exposure to sunlight/ultraviolet radiation. Most frequently reported occupations included armed services personnel (37%), agricultural workers (18%), and construction workers (9%). Cases associated with a single diagnosis showed a median time period of 61 y (range 24–71) between first exposure and case reporting. Most of these exposures occurred in the 1940s, in armed services personnel (war service), which is reflected in the age of individuals in THOR's case reports (median 80 y, range 43–98). Conclusions: There is little published information on latency for work-related skin neoplasia. Incident case analysis in THOR, and investigation of the time between exposure, symptom onset and diagnosis may help to address this, and contribute to the evidence base.